2018
DOI: 10.2993/0278-0771-38.4.533
|View full text |Cite
|
Sign up to set email alerts
|

“Listen Carefully to the Voices of the Birds”: A Comparative Review of Birds as Signs

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The survey results indicated that the villagers were not aware of the importance of the endangered Greater Adjutant. In many cultures around the world birds are considered to provide omens of the future (Hull and Fergus 2017;Wyndham and Park 2018). The stork was treated by the villagers as a bad omen because it feeds on the carcasses of animals and brings bones and debris to its nesting trees.…”
Section: Overview Of Conservation Programmentioning
confidence: 99%
“…The survey results indicated that the villagers were not aware of the importance of the endangered Greater Adjutant. In many cultures around the world birds are considered to provide omens of the future (Hull and Fergus 2017;Wyndham and Park 2018). The stork was treated by the villagers as a bad omen because it feeds on the carcasses of animals and brings bones and debris to its nesting trees.…”
Section: Overview Of Conservation Programmentioning
confidence: 99%
“…There are some who continue to communicate with birds and share bird talk stories. Bird talk is recognized on many levels-interpreted for prognosticating weather or death and disease, bearing messages, witnessing solemn occasions, or auguring good luck and well-being (Wyndham et al 2018). For the Embera of Panama (Kane 2015:35), bird songs and calls are located between the invisible and the human worlds as they inform people of new birth and impending death.…”
Section: First Voices and Silencesmentioning
confidence: 99%
“…It is generally accepted that based on data presented above, like other small ethnic societies around the world, Sundanese people of Kertasari, West Java, have local knowledge on folklore in relation with birds that are inherited from their ancestors and/or obtained from their experiences in their life and their close interaction with the local environment or local ecosystem (Kane 2015;Pam 2017;Wyndham and Park 2018).…”
Section: Folkloric Birdsmentioning
confidence: 99%